2012
DOI: 10.1016/j.juro.2012.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Laparoscopic Ablative Renal Surgery in Infants: Comparative Study with Children

Abstract: Laparoscopic ablative renal surgery is safe and feasible even in infants and small children. Intraoperative and postoperative complications are associated with approach and type of surgery, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…10 In this population, standard transperitoneal laparoscopic or retroperitoneoscopic HN approaches were recently reported to be safe and to have a low conversion rate. 11 Both approaches were shown to have equivalent operative times and lower analgesic requirements compared with that of an open surgical approach. 12 There have been few publications of studies describing RAHN, and none focus on how to carry out this type of surgery with small children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In this population, standard transperitoneal laparoscopic or retroperitoneoscopic HN approaches were recently reported to be safe and to have a low conversion rate. 11 Both approaches were shown to have equivalent operative times and lower analgesic requirements compared with that of an open surgical approach. 12 There have been few publications of studies describing RAHN, and none focus on how to carry out this type of surgery with small children.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some authors reported significant functional loss of the residual moiety, and advocated for the use of an open approach in children aged <1 year . In this population, standard transperitoneal laparoscopic or retroperitoneoscopic HN approaches were recently reported to be safe and to have a low conversion rate . Both approaches were shown to have equivalent operative times and lower analgesic requirements compared with that of an open surgical approach .…”
Section: Introductionmentioning
confidence: 99%
“…Experience with laparoscopic renal surgery in infants younger than 12 months or those weighing less than 10 kg at the time of surgery is described by You et al (page 1330) from Republic of Korea. 3 They performed 25 procedures in infants who met these criteria using a transperitoneal or retroperitoneal approach. The majority of patients underwent nephrectomy or nephroureterectomy with 10 infants undergoing heminephrectomy.…”
Section: Feasibility Of Laparoscopic Ablative Renal Surgery In Infantsmentioning
confidence: 99%